A politico-legal framework for integration in Africa : exploring the attainability of a supranational African Union - Fagbayibo, Babatunde Olaitan (University of Pretoria, 2010)
The emergence of the African Union (AU) is seen as an effort to reposition Africa for the challenges of contemporary global realpolitik and, in particular, it provides a road map towards the attainment of a political union. The institutional architecture of the AU, modelled after the European Union (EU), indicates an intention on the part of the architects of the AU to endow the organisation with supranational attributes. However, none of its institutions has as yet started to exercise supranational powers. It is against this background that this thesis explores the feasibility of transforming the AU from a mere intergovernmental organisation into a supranational entity. In the course of the investigation, it was found that a major obstacle to realising this is the absence of shared democratic norms and standards, a consequence of the unconditional membership ideology of the AU. This thesis argues that the starting point of closer integration in Africa should be the cultivation and adoption of shared norms and values. To address this, the study proposes that the AU design an institutional mechanism for regulating its membership. Using the African Peer Review Mechanism (APRM) as a case study, this study shows that it is possible to establish a regulatory regime based on strict adherence to shared fundamental norms and values. A major recommendation is the transformation of the APRM into a legally binding instrument for setting continental democratic standards, assessing whether member states fulfil these standards and ultimately determining which member states are qualified, based on objective standards, to be part of a democratic AU.
https://repository.up.ac.za/handle/2263/28573
Keywords: African Union; African peer review mechanism; Regional economic communities (RECs); Regional integration

Développement et intégration régionale en Afrique de l'Ouest : analyse des contributions de l'OHADA et de l'UEMOA - N'Guessan, Donald Jean-Marc (Université de Reims Champagne-Ardenne, 2010)
L'intégration juridique apparaît telle une prometteuse locomotive de l'intégration économique. La confiance que le droit OHADA devrait susciter chez les opérateurs économiques, en procédant progressivement à la sécurisation juridique et judiciaire du marché commun de I'UEMOA, devrait les inciter à y créer et développer des activités économiques. Ce, en quoi nous nous interrogeons de savoir si le droit des affaires OHADA peut être productif de dynamique économique par l'investissement privé direct étranger ou national, considéré au troisième millénaire comme le moteur de la croissance, dans l'espace UEMOA, libre de circulation. Dans l'optique de cette démarche sécuritaire et impulsive, I'OHADA et I'UEMOA vont participer à I'édification de ce cadre juridique communautaire au travers d'un dispositif conçu autour de quatre axes, à savoir : un dispositif de sécurité organisationnelle capable de garantir la solidité et le fonctionnement autonome et pérenne des institutions communautaires chargées de conduire le projet d' intégration à sa réalisation ; la consécration d'une intégration juridique relative aux affaires, comme outil fondamental de consolidation de l'intégration économique : l'édification de structures communautaires chargées de défendre ce droit dont l'application est déterminante à la sécurité dans les relations d'affaires ; enfin, I'instauration d'une liberté de circulation dans tout I'espace communautaire afin de favoriser les échanges intracommunautaires, indispensables à la dynamique juridico-économique régionale , et dont l'analyse devrait permettre d'apprécier le niveau de réalisation et la fonctionnalité de cette plateforme OHADA-UEMOA.
Keywords: Afrique occidentale; Intégration économique; OHADA; Organisation pour l'harmonisation en Afrique du droit des affaires; UEMOA; Unification internationale; Union économique et monétaire Ouest africaine; WAEMU